(untitled) (Economic and Political Thought, 2019)
The article discusses the influence of the European migration crisis on Poland’s foreign policy in the period 2015–2018. The research aims to answer the question to what extent and level and under the influence of what factors the immigration crisis of 2015 had impact on the foreign policy of the Republic of Poland. The first part of the article analyses the reasons and the course of the immigration crisis of 2015. The next part presents the evolution of Poland’s stance on the immigration crisis. The final part of the article contains main conclusions.